2013
DOI: 10.1002/adma.201301461
|View full text |Cite
|
Sign up to set email alerts
|

Large Magnetoresistance in Magnetically Coupled SrRuO3 –CoFe2O4 Self‐Assembled Nanostructures

Abstract: A new way to induce a large magnetoresistance has been achieved by self-assembled nanostructures consisting of ferromagnetic spinel CoFe₂O₄ (CFO) and metallic perovskite SrRuO₃ (SRO). The interdiffused Fe³⁺ ions in SRO have paved the way to strong magnetic couplings with CFO nanopillars, resulting in the suppression of spin-polarized electron scattering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Artificially constructed horizontal oxide heterointerfaces in the form of superlattices, multilayers, and/or heterostructures have been widely investigated to manipulate physical properties789. Recently, nanocomposites with a vertical interface network are emerging as an alternative approach to tune physical properties since microstructure, interfacial coupling, and lattice strain can be tailored from 2D to 3D10111213141516171819. The lack of substrate clamping effect and the presence of large interfacial area in thick vertically aligned nanocomposite films in comparison with conventional horizontal heterostructures make such a new 3D architecture attractive20 to tune the functionalities of materials21.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Artificially constructed horizontal oxide heterointerfaces in the form of superlattices, multilayers, and/or heterostructures have been widely investigated to manipulate physical properties789. Recently, nanocomposites with a vertical interface network are emerging as an alternative approach to tune physical properties since microstructure, interfacial coupling, and lattice strain can be tailored from 2D to 3D10111213141516171819. The lack of substrate clamping effect and the presence of large interfacial area in thick vertically aligned nanocomposite films in comparison with conventional horizontal heterostructures make such a new 3D architecture attractive20 to tune the functionalities of materials21.…”
mentioning
confidence: 99%
“…The structural, optical, and magnetic properties can be also tuned by film thickness363738. However most of the previous studies on heteroepitaxial oxide nanocomposite films focus on varying phase compositions3940, substrate orientations2441, material systems14424344, substrate lattice parameter and symmetry11294546, etc. The thickness effect, a key factor in composite films, is rarely studied.…”
mentioning
confidence: 99%
“…For PMN‐PT compositions near the MPB, mixed phases are known, where structurally bridging monoclinic (M) states exist between T and R phases . Large piezoelectricity and dielectric properties result …”
Section: Introductionmentioning
confidence: 99%
“…A CoFe 2 O 4 ‐SrRuO 3 (CFO‐SRO) nanopillar heterostructure has recently been reported that consists of CFO nanopillars within a SRO matrix . In this heterostructure, the SRO serves as a conductive material and CFO as an insulating one.…”
Section: Introductionmentioning
confidence: 99%
“…[30,31] To meet the criteria for practical applications, previous works have pointed out that the grain boundary in polycrystalline manganite can induce the spin tunneling and thus results in the enhanced MR in a relatively low magnetic field (H < 1 T). [32][33][34][35] Taking the advantage of mesocrystal-embedded system that possesses uniform artificial boundaries, Liu et al [36] observed an unexpectedly large MR in the magnetic mesocrystal-embedded SRO system. The correlation between the magnetic CFO mesocrystal and SRO matrix was investigated via the measurements of field-dependent transport [ Fig.…”
Section: Multifuncationality Modulated Via An Embedment Of Mesocrystalsmentioning
confidence: 99%